The Professional Dilemma : Respect for the Rules or Being Human(e)? A Case Analysis - Datta, Sugata; Jagadeesha, M. (Prabandhan: Indian Journal of Management, 2018)
This case study was about how desperate one can be to seek employment in a premier organization. The urge to move ahead from being tagged as an unemployed youth and getting recognised as â€œemployedâ€ was so acute that it did not deter the candidate from resorting to unfair means. Everything may be fair in love and war, but when it comes to employment in a public sector undertaking, things can really turn ugly, if the means to the end are not fair. This case study intended to create an awareness among students and professionals that integrity and sincerity are not mere virtues to be included in their resume, but are to be practiced in life. While India is growing and job opportunities are improving, we should not lose focus of the ancient values and ethics which are so deep rooted in the Indian culture and ethos.